1993
DOI: 10.1111/j.1476-5381.1993.tb12879.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide‐mediated hyporeactivity to noradrenaline precedes the induction of nitric oxide synthase in endotoxin shock

Abstract: 1 The role of an enhanced formation of nitric oxide (NO) and the relative importance of the constitutive and inducible NO synthase (NOS) for the development of immediate (within 60 min) and delayed (at 180 min) vascular hyporeactivity to noradrenaline was investigated in a model of circulatory shock induced by endotoxin (lipopolysaccharide; LPS) in the rat. 2 Male Wistar rats were anaesthetized and instrumented for the measurement of mean arterial blood pressure (MAP) and heart rate. In addition, the calcium-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
276
4

Year Published

1995
1995
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 389 publications
(299 citation statements)
references
References 40 publications
19
276
4
Order By: Relevance
“…Moreover, an increase in nitrotyrosine immunoreactivity was recently found in the lung of rats injected with bacterial endotoxin [18]. It is noteworthy in this contest that among many organs studied, the lung expresses the highest specific activity of iNOS in response to endotoxin injection in the rat [10]. Thus, it appears that endotoxin shock results in induction of iNOS, with subsequent formation of peroxynitrite.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Moreover, an increase in nitrotyrosine immunoreactivity was recently found in the lung of rats injected with bacterial endotoxin [18]. It is noteworthy in this contest that among many organs studied, the lung expresses the highest specific activity of iNOS in response to endotoxin injection in the rat [10]. Thus, it appears that endotoxin shock results in induction of iNOS, with subsequent formation of peroxynitrite.…”
Section: Discussionmentioning
confidence: 73%
“…Tissues were then homogenized in the buffer on ice using a Tissue Tearor 985-370 homogenizer (Biospec Products, Racine, WI). Conversion of [3H]L-arginine to [3H]L-citrulline was measured in the homogenates as described [10]. Briefly, cell homogenate (30 pl) was incubated in the presence of [3H]L-arginine (10pM, 5 kBq/tube), NADPH (1 mM), calmodulin (30 nM), tetrahydrobiopterin (5 gM) and calcium (2 mM) for 30 min at 22°C.…”
Section: Nitric Oxide Synthase Assaymentioning
confidence: 99%
“…Endotoxaemia also resulted in a rapid and sustained increase in plasma NO2-(breakdown product of NO) levels, which were significantly higher than in sham-operated controls between 30 and 180 min after the start of the endotoxin infusion. This increase in plasma NO2-is due to an enhanced formation of NO arising from both activation of the constitutive NOS (early phase) as well as the induction of NOS (delayed phase) (Szabo et al, 1993). The finding, however, that endotoxaemia was not associated with a significant rise in plasma nitrate levels is not entirely surprising, for NO2-is the predominant metabolite of NO (Ignarro et al, 1993).…”
Section: Mortalitymentioning
confidence: 99%
“…Endotoxin leads to the induction of a calcium-independent nitric oxide (NO) synthase (NOS) (Szabo et al, 1993;JulouSchaeffer et al, 1991) resulting in an overproduction of the vasodilator. This excessive formation of NO contributes importantly to the severe hypotension seen in endotoxin shock (Thiemermann & Vane, 1990; see Thiemermann, 1994 for review).…”
Section: Introductionmentioning
confidence: 99%
“…6 Enhanced formation of NO following induction of iNOS contributes importantly to the circulatory failure and cardiovascular dysfunction, such as vasodilatation, severe hypotension and vascular hyporeactivity to vasoconstrictor agents, in various animal models of septic shock. 7 Ketamine, a phencyclidine derivative, has been recommended for the induction of anaesthesia and sedation in patients with circulatory shock because of its actions in increasing sympathetic nervous system activity, to maintain blood pressure, and in preserving cardiovascular function, s-n In addition, a recent study demonstrated that ketamine suppressed TNF-0t production induced by endotoxin in cultured macrophages and inhibited NO-dependent cGMP production in cultured cerebral neuron. 12,13 More recently, ketamine has been reported to inhibit accumulation of nitrite, one of the metabolites of NO, dose-dependently in LPS-activated macrophages.…”
mentioning
confidence: 99%